The Role of Non-Profit Organizations in Managing the Covid-19 Pandemic in West Nusa Tenggara Province: A Study on MCCC NTB and LAZDASI NTB - Maulana Rahmat Fajar; Rahmad Hakim; Arif Luqman Hakim (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
The aim of this research is to conduct an in-depth analysis regarding the role of non-profit organizations in overcoming the Covid-19 pandemic in West Nusa Tenggara Province, especially at the MCCC NTB and LAZDASI NTB institutions. This type of research is descriptive qualitative, this research uses data collection through observation, interviews, literature study and documentation. The analytical methods used are data collection, condensation, data presentation, and drawing conclusions. The results of this research found that the role of non-profit organizations in overcoming the Covid-19 pandemic in West Nusa Tenggara Province for the period April - December 2020, in this case the roles or activities carried out by MCCC NTB are as follows: 1) Muhammadiyah Hospital and Clinic Services, 2) distributing masks, 3) distributing hand sanitizer, 4) distributing PPE (personal protective equipment), 5) providing hand washing facilities in the community, 6) providing online educational facilities, 7) distributing educational posters, 8) spraying disinfectants, 9) Providing basic food assistance. The roles played by LAZDASI NTB in preventing Covid-19 are: 1) Free mask assistance, 2) Hand sanitizer assistance, 3) Covid-19 ambulance service, 4) Disinfectant spraying, 5) Portable wash basins, 6) Implementation education Health Protocols, 7) Affected Food Packages, 8) Independent partners. Based on this, the strategy for handling Covid-19 is in accordance with the guidelines created by the government.